OPTIMALISASI PENGELOLAN BADAN USAHA MILIK DESA TERHADAP PENINGKATAN PEMBANGUNAN EKONOMI DI DESA BOIYA KECAMATAN MAIWA KABUPATEN ENREKANG - Sukena Sukena; Pratiwi Ramlan; Andi Uceng (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The research objective is to determine the Optimization of Management of Village Owned Enterprises in Increasing Economic Development in Boiya Village, Maiwa District, Enrekang Regency and the factors that influence it. Data collection techniques using observation, questionnaire, interview, and library research. The population in this study using saturated samples with as many as 40 respondents, data processing techniques using quantitative descriptive research type. Data analysis technique used is descriptive statistics and with the help of SPSS version 21 application. The results showed that the Optimization of Management of Village Owned Enterprises affected the village Economic Development of 60.45% in the unfavorable category. While the results of the Economic Development analysis of 59% are in the unfavorable category. Factors affecting the management of Village-Owned Enterprises: 1). Communication factor 56.5%. 2). Local community empowerment factor 66%. 3). Managerial capacity factor is 60%. 4). The BUMDes infrastructure factor is 61.4%. 5). Transparency factor 62%. 6) accountability factor 58%. Based on the description above, it can be concluded that the factors that influence the management of Village Owned Enterprises in Boiya village, Maiwa District, Enrekang Regency with a percentage of 60% are in the unfavorable category.